2019
DOI: 10.1007/s00167-019-05526-y
|View full text |Cite
|
Sign up to set email alerts
|

Three days of training with a low-fidelity arthroscopy triangulation simulator box improves task performance in a virtual reality high-fidelity virtual knee arthroscopy simulator

Abstract: Purpose The aim of this work is to evaluate the effectiveness of training with the low-fidelity ArthroBox ® regarding performance of different basic arthroscopy tasks using a validated high-fidelity virtual reality simulator of the knee. Methods Nineteen volunteers (14 females and 5 males) without any previous experience in arthroscopy were randomly assigned either to the ArthroBox ® training group (n =10) or the non-training group (n =9). The training group underwent a supervised ArthroBox ® training consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
0
14
1
1
Order By: Relevance
“…Our findings are somewhat contrary to those of Bouaicha et al, 5 who, in a group of arthroscopy-naïve medical students, found that three 1-hour training sessions on a lowfidelity arthroscopy simulator box resulted in improved performance on a high-fidelity computer-assisted knee arthroscopy simulator as compared with no training. It would be interesting to compare the low-fidelity simulator box-trained group with a group spending the same amount of time training on more complex procedure-specific tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are somewhat contrary to those of Bouaicha et al, 5 who, in a group of arthroscopy-naïve medical students, found that three 1-hour training sessions on a lowfidelity arthroscopy simulator box resulted in improved performance on a high-fidelity computer-assisted knee arthroscopy simulator as compared with no training. It would be interesting to compare the low-fidelity simulator box-trained group with a group spending the same amount of time training on more complex procedure-specific tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…14 Previous studies have determined that residents' performance in both the operating room and simulation-based laboratories improved after training on validated arthroscopic simulators, which demonstrated both validation and transferability. [15][16][17][18][19][20][21] However, little research has investigated the retention of arthroscopic skills. In addition, many studies that have focused on the retention of surgical skills, including laparoscopic skills, have demonstrated significant deterioration in skills when not practiced over a long period.…”
Section: See Commentary On Page 2873mentioning
confidence: 99%
“…In a range of educational settings, VR-based training consistently increased student engagement and motivation (23,24). Further, VR applications are effective at training practical skills (25,26) and knowledge development (27)(28)(29). While VR has previously been applied in the context of both stroke management and medical education (30)(31)(32), applications for stroke have primarily targeted patients (e.g., for limb rehabilitation) rather than healthcare professionals [reviewed in (33,34)].…”
Section: Introductionmentioning
confidence: 99%